2016
DOI: 10.1186/s13046-016-0326-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXCR4 by a selective peptide antagonist modulates tumor microenvironment and microglia reactivity in a human glioblastoma model

Abstract: BackgroundThe CXCL12/CXCR4 pathway regulates tumor cell proliferation, metastasis, angiogenesis and the tumor-microenvironment cross-talk in several solid tumors, including glioblastoma (GBM), the most common and fatal brain cancer. In the present study, we evaluated the effects of peptide R, a new specific CXCR4 antagonist that we recently developed by a ligand-based approach, in an in vitro and in vivo model of GBM. The well-characterized CXCR4 antagonist Plerixafor was also included in the study.MethodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 56 publications
3
68
0
Order By: Relevance
“…Plerixafor strongly decreased the CXCR4 expression on cell membrane of U87MG cells treated for 24h compared to untreated (CTRL) cells (Fig 1C, green fluorescence) as already reported [11]. However, at 48h of treatment with this antagonist the CXCR4 receptor was already re-expressed on cell membrane and its level was further increased at 72h (Fig 1C).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Plerixafor strongly decreased the CXCR4 expression on cell membrane of U87MG cells treated for 24h compared to untreated (CTRL) cells (Fig 1C, green fluorescence) as already reported [11]. However, at 48h of treatment with this antagonist the CXCR4 receptor was already re-expressed on cell membrane and its level was further increased at 72h (Fig 1C).…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, we recently investigated the role of CXCR4 in glioma-microenvironment interactions and demonstrated that reducing CXCR4 expression in human U87MG cells promoted M1 features in microglia/macrophages recruited to the tumor area, creating an environment potentially less favorable for tumor growth [11]. …”
Section: Discussionmentioning
confidence: 99%
“…These beneficial effects relied on reduced GAMs' infiltration at the tumor site and increased antitumor activities [63] . Inhibition of the C-X-C chemokine receptor type 4 (CXCR4) by a newly synthetized receptor antagonist, peptide R, reduced tumor growth, glioma cell invasiveness, and intratumor vessel formation while directing GAMs' immune activation toward a pro-inflammatory/antitumor phenotype [64] . Notably, SDF-1 suppression in a murine glioma resulted in delayed tumor growth and invasiveness, lower microvascular density, and higher density of microglia/macrophages in non-hypoxic compared to hypoxic regions.…”
Section: Drugs That Interfere With Gams' Inflammatory Activation and mentioning
confidence: 99%
“…CXCR4, an important player in supportive interactions between tumor cells and other cells, participates in tumor cell proliferation, metastasis, angiogenesis, and the tumor microenvironment cross-talk in GBM. Studies have revealed that targeting the CXCR4 pathway may provide a therapeutic approach against glioma (12,38). Our data suggested that FTY720 can block the cross-talk between glioma and GAMs by increasing microglial CXCR4 internalization rather than by affecting CXCL12 secretion by glioma.…”
Section: Discussionmentioning
confidence: 67%